The effect of Ni additions on the oxidation behaviour of Co–Re–Cr high-temperature alloys. (4th May 2018) - Esleben, K.; Gorr, B.; Christ, H.-J.; Mukherji, D.; Rösler, J.
Abstract: The present study focused on the influence of Ni on the microstructure and oxidation behaviour of Co–Re–Cr-based alloys. Alloys with three different Ni contents were tested in laboratory air at 800–1100 °C. A refinement and a reduction of the σ phase volume fraction as well as a change in the matrix microstructure were observed. Thermogravimetric measurements showed that the alloys with higher Ni contents possess a better oxidation resistance when exposed to higher temperatures. All alloys suffered from continuous mass loss during oxidation at 800 °C due to the formation of porous oxides scales, consisting of Co3 O4, Co(Ni)O and Ni-doped CoCr2 O4, which allow the evaporation of Re-oxides. At 900–1100 °C, only the alloy with 25 at. % Ni showed parabolic oxidation kinetics after a short period of transient oxidation. This is a result of the fast formation of a protective Cr2 O3 layer. It was also found that exposure to air at 1000 °C leads to a phase transformation of the bulk material; an oxidation-induced formation of fine hexagonal close-packed (hcp) grains was observed near the oxide scales. It is supposed that the improved oxidation resistance of Ni-containing Co–Re–Cr alloys is a result of enhanced Cr diffusion caused by the Ni addition. The extensive formation of the fcc phase in the alloy matrix had a detrimental effect on the oxidation behaviour of the Ni-containing Co–Re–Cr-based alloys.